Teaching and Learning Resources for Endangered Languages - Rushengul Urayim (University of Windsor, 2024)
Previous research on endangered languages (EL) has focused on two areas: documentation and revitalization (REHG & Campbell 2018). For revitalization, it is essential to create teaching and learning materials (TLM), yet there is limited research on this topic. This volume, a follow-up from the Foundation for EL 24th annual conference, addresses this imbalance.